A Prototype Design of a Wireless Capsule Endoscope. Issue 4 (8th July 2010) - Chan, Y.; Meng, M. Q.-H.; Wang, X.; Wu, J. C.-Y.
Abstract : Diseases of the gastrointestinal tract, such as intestinal bleeding and ulceration, are very common. To determine the location of the disease, as well as to diagnose the problem, endoscopy is performed. A wireless capsule endoscope is a pill-sized device that is easily swallowed by the patient. It is equipped with a camera and a wireless transmitter so that as it travels through the patient's gastrointestinal tract, it takes pictures or video images of the tract and transmits the information out of the patient's body. This article discusses the possible solutions and challenges of a wireless capsule endoscope in terms of the choice of wireless frequency and circuit components. A prototype is built with commercially available components to demonstrate the concept of the device.